Stress proteins and auxiliary anti-stress compounds in intertidal macroalgae Proteínas de estrés y compuestos anti-estrés auxiliares en algas marinas intermareales - Edgardo Cruces; Pirjo Huovinen; Iván Gómez (Latin American Journal of Aquatic Research, 2012)
Intertidal macroalgae are exposed to strong variation in the physical environment and thus, diverse anti-stress mechanisms are displayed by these organisms. Stress proteins (also called heat shock proteins, HSPs) have been invoked as potential protective mechanism, especially during stressful action of temperature and solar radiation. Therefore, macroalgae have not normally been used as model organisms in studies of these molecules. The present study compiles the existing information from intertidal species in the context of major factors that have been reported to induce them, e.g. temperature, enhanced solar radiation, contaminants, etc. Additionally, in order to address the question whether the expression of these proteins operates in intertidal macroalgae complementarily with other protective mechanisms, a case study of induction of HSPs after exposure to UV radiation and high temperature in two upper littoral species, Ulva sp. and Porphyra columbina, from southern Chile is presented. In parallel, two well-known responses to stress, photoinhibition of photochemical reactions (Fv/Fm) and ROS scavenging were measured. The results indicated that, although stress proteins were detected in a time span between 3 and 24 h, the responses were not correlated with photochemical and antioxidative response. Overall, the study outlines a potential role of stress proteins in ecophysiological responses developed to cope mainly with high temperature and UV radiation. However, other rapid metabolic adjustments (e.g. high thermo-tolerance of photosynthesis and efficient ROS scavenging), together with other biomolecules (mycosporines, phenols, polyamines, etc.) and morpho-functional adaptations to the intertidal life (e.g. small size, high area/volume ratio) are also important. Las macroalgas marinas intermareales están expuestas a extrema variación en las condiciones ambientales y por ello desarrollan una serie de mecanismos anti-estrés. Las proteínas de estrés (HSPs) han sido consideradas como potenciales agentes protectores en respuesta a condiciones estresantes, especialmente durante la acción de elevada temperatura y alta radiación solar. Considerando que las macroalgas marinas no han sido usadas comúnmente como modelos de estudio para analizar estas moléculas, el presente trabajo compila la información existente sobre la inducción de proteínas de estrés en algas intermareales en el contexto de los principales factores hasta ahora reportados como inductores, e.g. temperatura, alta radiación solar, contaminantes, etc. Adicionalmente, mediante un estudio de caso usando dos especies del intermareal superior, Ulva sp. y Porphyra columbina colectadas en el sur de Chile, se examina si la inducción de proteínas de estrés ocurre de forma complementaria con otras respuestas anti-stress. Para ello, dos mecanismos bien conocidos, fotoinhibición de fotosíntesis y actividad antioxidante, fueron medidos en paralelo. Los resultados indicaron que, aunque hubo expresión de proteínas de estrés dentro de un periodo experimental entre 3 y 24 h, estas respuestas no fueron correlacionadas con cambios en fotosíntesis o actividad antioxidante. En general, el estudio perfila un potencial rol de estas moléculas en algunas respuestas ecofisiológicas desarrolladas para contrarrestar los efectos negativos de las altas temperaturas y la radiación solar. Por otro lado, otros ajustes metabólicos de acción rápida (e.g. fotoinhibición y actividad antioxidante), distintas biomoléculas (micosporinas, fenoles, poliaminas, etc.), además de las adecuaciones morfo-funcionales a la vida intermareal (e.g. pequeno tamano, alta proporción área/volumen) son importantes para explicar la fisiología de estos organismos.